Mechanical Regulation of Bone Regeneration: Theories, Models, and Experiments - Betts, Duncan Colin; Müller, Ralph (Frontiers in Endocrinology, 2014)
How mechanical forces influence the regeneration of bone remains an open question. Their effect has been demonstrated experimentally which has allowed mathematical theories of mechanically driven tissue differentiation to be developed. Many simulations driven by these theories have been presented, however validation of these models has remained difficult due to the number of independent parameters considered. An overview of these theories and models is presented along with a review of experimental studies and the factors they consider. Finally limitations of current experimental data and how this influences modelling are discussed and potential solutions are proposed.